Listen for the lie - Tintera, Amy (Celadon Books, 2024)
"What would you do if you thought you murdered your best friend? And if everyone else thinks so too? What if the truth doesn't matter? As Lucy Chase's Texas hometown begins to tell versions of what happened and who Lucy is to a nationwide, true crime obsessed audience, at the bequest of her grandmother, she returns to the place she vowed never to set foot in again to solve her friend's murder, even if she is the one that did it"